2019
DOI: 10.1016/j.conctc.2019.100359
|View full text |Cite
|
Sign up to set email alerts
|

Design and methods for the Ranger Resilience and Improved Performance on Phospholipid bound Omega-3's (RRIPP-3 study)

Abstract: Intake of nutrients fundamental for optimal neuronal function is of increasing interest. The potential importance of omega-3 highly unsaturated fatty acids (HUFAs) for optimizing emotional states, cognitive function, and mental health has been demonstrated in observational studies and randomized controlled trials. Omega-3 (HUFAs), specifically EPA (eicosapentaenoic acid) and docosahexaenoic acid (DHA), are concentrated in neural tissues and are essential for neural function, normative neurodevelopment, neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Similarities between the PFC female resilient and male susceptible endothelial transcriptome profiles for this pathway and the fact that both subgroups maintain BBB integrity in this brain region despite chronic stress exposure suggest that it could play a protective role in stress-induced BBB permeability loss. With previous reports linking omega-3 fatty acid consumption with resilience to stress in rodents 52 and humans 53 , further studies are warranted to confirm their potential beneficial effect on the neurovasculature and gain mechanistic insights.…”
Section: Discussionmentioning
confidence: 96%
“…Similarities between the PFC female resilient and male susceptible endothelial transcriptome profiles for this pathway and the fact that both subgroups maintain BBB integrity in this brain region despite chronic stress exposure suggest that it could play a protective role in stress-induced BBB permeability loss. With previous reports linking omega-3 fatty acid consumption with resilience to stress in rodents 52 and humans 53 , further studies are warranted to confirm their potential beneficial effect on the neurovasculature and gain mechanistic insights.…”
Section: Discussionmentioning
confidence: 96%
“…The chicken and egg products were evaluated for taste and cooking acceptability by the Human Systems Integration and Sciences Division, U.S. Army Combat Capabilities Development Command-Soldier Center, Natick, MA, and received positive ratings. These same intervention foods were also used in a previous randomized controlled study [25] and were independently analyzed for nutritional content by Lipid Technologies, LLC, Austin, MN.…”
Section: Intervention Group Foodsmentioning
confidence: 99%
“…However, increasing n-3 HUFA intake by consuming oily fish and regular dietary supplementation does not remediate the excess n-6 PUFA in the diet. A fatty acid supplementation study using krill oil in military personnel failed to show treatment effect on outcomes due to poor compliance to n-3 pills [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we conducted the Ranger Resilience and Improved Performance on Phospholipid bound Omega-3’s study (RRIPP-3), a randomized controlled trial (RCT) of omega-3 supplementation from krill oil on cognition and resilience among young military officers. Methodology 7 and results 8 from this trial have been previously reported. A digital adaptation of the Stroop Color-Word Inhibition test 9 was employed as a co-primary outcome, and 7% performed below chance at baseline.…”
Section: Introductionmentioning
confidence: 99%